Isolation, fruiting and pathogenicity of marasmiellus palmivorus (Sharples) desjardin (comb. prov.) in oil palm plantations in West Malaysia - Pong, V. M.; Mior Ahmad, Zainal Abidin; Almaliky, Bushra Subair Abdulsada; Kadir, Jugah; Wong, Mui Yun (Universiti Putra Malaysia Press, 2012)
Malaysia`s golden crop, oil palm (Elaies guineensis), is susceptible to bunch rot disease caused by Marasmiellus palmivorus (Sharples) Desjardin (comb. prov.). Nonetheless, there is no published information on the morphology and pathogenicity of the species found in local oil palm plantations in Malaysia. Rhizomorphs and basidiocarps found on dead fronds or trunks were randomly sampled from the plantations located in the states of Perak and Selangor. Isolates were identified based on the morphology and molecular methods as Marasmiellus palmivorus and pure cultures subsequently produced similar fruit bodies (basidiocarps) by in vitro methods. Hyphal morphology was examined by light and scanning electron microscopy and found to be septate and produced clamp connections. White spore prints were obtained from each pileus. Naturally grown and induced basidiocarps were similar with diameter of pileus ranging from 1.0-2.8cm, slightly depressed at the centre, smooth, convex, with involute margin, orange-white fading to white and possessed a central, solid, cylindrical, tough, overall whitish stipes with length ranging from 0.8- 2.6cm. The gills were adnate, distant and have a non-distinctive odour. Basidiospores were ellipsoid in shape and spores were found to be viable with percentage germination of 80-85%. Upon germination, they produced germ tubes ranging from 64.3 – 82.5 µm after 24 h incubation at ambient temperature (27 ± 2°C) on water agar. Pathogenicity test of six isolates of Marasmiellus sp. positively produced necrotic symptoms on wounded leaves of oil palm seedlings.